Unusual lymphadenopathy diagnosed by endobronchial ultrasound-guided transbronchial needle aspiration - Stirpe, Emanuele; Bardaro, Floriana; Köhl, Johanna (Monaldi Archives for Chest Disease, 2022)
Oxidized cellulose, used as hemostatic in thoracic surgery, may cause in some cases foreign body reactions, and simulate other diseases. We report the case of a 39-year-old man operated on a middle lobe lobectomy for atypical carcinoid. The follow up chest-CT showed enlarged mediastinal lymph nodes, so endobronchial ultrasound-guided transbronchial needle aspiration was performed suspecting recurrence of the tumor. The cytology results showed amorphous fragments such as foreign body reaction secondary to Pahacel®, used as hemostatic during the surgery. A few days later, the patient was re-operated on suspicion of mediastinitis induced by the endoscopic procedure. The aim of this case is to consider the foreign body reaction to Pahacel®, in patients with postoperative thoracic lymphadenopathy. It is also important to remember that in these patients the endoscopic procedures allow the diagnosis but may cause mediastinitis.